APPLICATION OF PSYCHOLOGICAL PREFERENCE AND EMOTIONAL GUIDANCE IN THE PERFORMANCE OF FILM AND TELEVISION ART: AN ANALYSIS BASED ON BASED ON COGNITIVE PSYCHOLOGY - Xie, Dunru (Revista argentina de clínica psicológica, 2020)
The performance of film and television art enriches our life. The psychological preference and connoisseurship of the audience for film and television art may vary with age, gender, region and cultural background. Based on cognitive psychology, this study investigates the status quo of film and television art in the Internet era through a questionnaire survey, and explores the application of psychological preference and emotional guidance in the performance of film and television art. The results show that, from the perspective of cognitive psychology, the appreciation and evaluation of the audience for the performance of film and television art is a form of artistic accomplishment; the psychology and emotion of the audience is influenced by the plot, visual rhythm, special effects, color and animation of film and television art; the audience’s preference for film and television art is determined by the expressive force, infection, and the theme of performance. The research lays a theoretical basis for the quality and proliferation of film and television art.